PROSEDUR TERJEMAHAN KANDOUSHI OUTOU PADA KOMIK ONE PIECE KARYA EIICHIRO ODA DALAM BAHASA INDONESIA - Nola Sintia; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Kandoushi stated that outou has different functions so that the translation procedures used are different. There are fourteen procedures for translating Japanese kandoushi outou into Indonesian, while in this study two procedures were found, namely component analysis translation procedures and direct translation. Kandoushi outou is translated using the word for word translation method. This study aims to explain the procedure for translating Japanese kandoushi outou into Indonesian by the translator. The method used in this research is qualitative method. One Piece comics were used as the data source. The results of the data analysis of the kandoushi outou translation procedure in One Piece comics found that five data were translated using the component analysis translation procedure and three data using the direct translation procedure. Sou, soudana, arya, aie, saana were translated using the component analysis translation procedure. Un, e, fu-n are translated using the direct translation procedure.Key Words: Kandoushi Outou, Procedure Translation.